Estimating Workforce Disposal in the Italian Labour Market - Bruno Contini; Elisa Grand (Institute for the Study of Labor (IZA), 2014)
Italy's labour market suffers from a serious pathology, in addition to the increasing precariousness of the young workforce common to all EU member countries: flows from regular employment to non-employment are very often dead-ends. A vast number of young individuals who lose their job only a few months or years after their first hire enter the ranks of the long-term unemployed or leave the workforce altogether, never to regain regular employment even after as long as twenty years. Many join the ranks of the irregular economy, many drop out of the labour force. Workforce disposal refers to the process generating this pathology. Prolonged stagnation of the Italian economy is an important long run macroeconomic determinant of workforce disposal. But there are several factors that have an important impact in the short and medium run. In this study we set out to investigate such determinants. Workforce disposal is present also in Spain, though to a lesser extent than Italy. Informed media report that similar developments are taking place also in countries of Eastern Europe, although no scientific evidence is yet available. And it would be surprising if the economies of Portugal and Greece were immune from the disease. Our exploration of the Italian case makes use of the WHIP longitudinal database originating from Social Security records.
Keywords: J2; J08; J20; J6; J63; J64; 330; unemployment; youth employment and participation; mobility; workforce